PROSPECTS OF THE HEALTHCARE DEVELOPMENT OF UKRAINE IN THE CONTEXT OF USING NEW INFORMATION TECHNOLOGIES - Kinash, Iryna Petrivna; Savchuk , Lilia (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2021)
The article is aimed at substantiating the prospects of the development of health care in Ukraine in the context of the use of new information technologies. The accuracy of considering such perspectives lies in the context of the approved Strategy for Information Society Development and Sector Reform. The following tendencies are revealed: introduction of automated information systems in the researched sphere was started; telemedicine and personalized medicine were developed; public health monitoring systems are being improved; new computer technologies are created and implemented for disease prevention, diagnostics, treatment processes; public electronic medical resources are created. It is emphasized that the use of information and communication technologies requires sufficient resources. The following promising areas of development are proposed: the spread of e-TB Manager technology, which allows you to treat at a distance or help to quickly transfer data about the patient from the ambulance to the hospital; active use of the automated information system on pharmacovigilance. Emphasis is placed on the formation of citizens' approach to "smart health". It can be implemented through the use of: fitness bracelets; antibacterial personal air purifiers; wireless headphones with a brain stimulator; smart cardiographs; smart scales, vitamin trackers, smart skipping ropes, etc. It is substantiated that successful informatization in the field of health care will largely depend on staffing. It is important to form the relevant competencies in the staff. Attention is paid to the development of the Institute of Public Health. It is concluded that proper economic support of health care, active introduction of new information technologies, cooperation of physicians and citizens, purposeful formation of human health culture will form the future of the research sphere.